Does China’s Rise influence anti-Americanism? Evidence from Colombia - Johnson, Gregg; Lin, Zhimin (Revista Latinoamericana de Opinión Pública, 2023)
China greatly expanded its presence in Latin America over the last several decades, with most researchers examining China’s economic and political efforts. Many U.S.-based researchers, pundits, and policymakers saw China as a potential rival and threat to U. S. hegemony. However, few researchers have examined how average Latin Americans viewed these changes. Building on theories of anti-Americanism, we examine whether views of China are associated with anti-Americanism in Colombia. Drawing on an original survey of Colombians, we find that China’s economic model, respondent ideology, and views of Chinese trade and business are weakly associated with anti-Americanism. Other factors have no association. Our findings provide an important early look into the effectiveness of China’s soft power in the region and contribute to the field’s understanding of anti-Americanism in the region.